2021
DOI: 10.3390/s21186245
|View full text |Cite
|
Sign up to set email alerts
|

Validity, Reliability and Sensitivity to Change of Three Consumer-Grade Activity Trackers in Controlled and Free-Living Conditions among Older Adults

Abstract: Wrist-worn consumer-grade activity trackers are popular devices, developed mainly for personal use. This study aimed to explore the validity, reliability and sensitivity to change of movement behaviors metrics from three activity trackers (Polar Vantage M, Garmin Vivoactive 4s and Garmin Vivosport) in controlled and free-living conditions when worn by older adults. Participants (n = 28; 74 ± 5 years) underwent a videotaped laboratory protocol while wearing all three trackers. On a separate occasion, participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“… 44 , 45 Therefore, we suggest that when measuring MVPA in community-dwelling older adults, other accelerometers should be considered. 3 , 53 Additionally, if a large variation in PA within their sample is expected, researchers should consider using both the activPAL and a wrist-worn accelerometer.…”
Section: Discussionmentioning
confidence: 99%
“… 44 , 45 Therefore, we suggest that when measuring MVPA in community-dwelling older adults, other accelerometers should be considered. 3 , 53 Additionally, if a large variation in PA within their sample is expected, researchers should consider using both the activPAL and a wrist-worn accelerometer.…”
Section: Discussionmentioning
confidence: 99%
“…Also, when using polysomnography as a criterion method, other brands of activity trackers tend to overestimate sleep time and underestimate wake time after sleep onset [ 45 , 46 ]. A recent study investigated the validity of three consumer activity trackers, including Garmin Vivosport, in older adults and found that all three activity trackers had a high level of accuracy for measuring sleep time [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absolute reliability was established as the degree of agreement in terms of precision of the individual measurements and reported as minimal detectable changes (that was calculated using standard error of measurement). Responsiveness was established as the ratio between minimally clinically important change on the measure and mean squared error of the response obtained from an analysis of variance model and reported as Guyatt's responsiveness (GR) coefficient [28].…”
Section: Clinimetric Propertiesmentioning
confidence: 99%
“…Bland-Altman plots [28][29][30][31] or modified Bland-Altman plots [32,33] described limits of agreement and systemic errors. Construct validity was tested between step counts and moderate-to-vigorous PA and was reported as correlation, r s (Spearman's Rho).…”
Section: Clinimetric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation